2022
DOI: 10.3389/fcvm.2022.821928
|View full text |Cite
|
Sign up to set email alerts
|

Significant Prediction of In-hospital Major Adverse Events by D-Dimer Level in Patients With Acute Type A Aortic Dissection

Abstract: BackgroundAcute type A aortic dissection (ATAAD) is a rare, life-threatening condition affecting the aorta. This study explores the relationship between the level of admission D-dimer, which was assessed during the first 2 h from admission, and in-hospital major adverse events (MAE) with ATAAD.MethodsA total of 470 patients with enhanced computed tomography (CT) confirmed diagnosis of ATAAD who underwent operation treatment in Guangdong Provincial People's hospital between September 2017 and June 2021 were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In addition, Tang et al also discovered that elevated D-dimer is an independent predictor of unfavorable in-hospital outcomes in patients with ATAAD (22). According to the findings of this research, patients with ATAAD may have higher D-dimer levels, which is in line with earlier studies and might be a predictive sign of poor results (20)(21)(22), despite the fact that the disparity was not statistically significant, perhaps a larger sample size will be required to test it again.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, Tang et al also discovered that elevated D-dimer is an independent predictor of unfavorable in-hospital outcomes in patients with ATAAD (22). According to the findings of this research, patients with ATAAD may have higher D-dimer levels, which is in line with earlier studies and might be a predictive sign of poor results (20)(21)(22), despite the fact that the disparity was not statistically significant, perhaps a larger sample size will be required to test it again.…”
Section: Discussionsupporting
confidence: 89%
“…D-dimer has been demonstrated in recent years to be significant for prognostication in a variety of cardiovascular illnesses (17,18). D-dimer testing has already been advised for the rule-out of ATAAD since earlier research has demonstrated a strong link between increased Ddimer levels and in-hospital death (19)(20)(21)(22). As said by Feng et al, increased D-dimer levels were found to be independently related to in-hospital major adverse events and can, therefore, be employed as a helpful predictive biomarker prior to operation with ATAAD (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 B). Feng et al demonstrated that an D-dimer level was an independent risk factor for acute kidney failure, MODS (multiple organ dysfunction syndrome), gastrointestinal bleeding, and mortality (D-dimer >14.5 mg/ml) [ 40 ]. Liu et al also found that an elevated D-dimer level at the time of admission was associated with the risk of postoperative complications occurred within 90 days in patients with ATAAD who underwent TAR and FET [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer has turned out to be effective in distinguishing AD from other diseases, and its levels were positively correlated with AD mortality risk [24]. However, some AD patients may present negative D-dimer levels [25,26], which underlines the necessity of utilizing a combination of diagnostic methods for accurate AD detection.…”
Section: Ad Risk Prediction According To the Aade Scorementioning
confidence: 99%